Delay Cost and Incentive Schemes for Multiple Users - Radhakrishnan, Suresh; Balachandran, Kashi R. (Management Science, 1995)
This paper examines the role of cost application in the presence of delay and agency costs. Two risk neutral division managers share a common (production) facility and decide on (a) the demand (usage) rates, and (b) productive action. Each division manager causes costly delays at the common production facility for the other division manager. The expected delay depends on the demand rates chosen by the division managers. An M/G/1 queuing framework is used to characterize delay costs. The unobservability of demand rates leads to stochastic choice hazard, and the unobservability of productive actions leads to moral hazard problems. The headquarters designs incentive schemes such that the use of the common facility is optimal for the firm. We show that a franchise contract is necessary to implement the first-best solution (similar to Harris and Raviv 1979), but is not sufficient. Specifically, when the action aversion of one division manager is small, the use of a franchise contract leads to “greedy” behaviour by the that division manager. The cost application required is greater than the expected marginal cost of delay to preclude the greedy behavior and ensure a stable equilibrium.